Satisfaction and adherence to pharmacological treatment for glycemic control in adults - Leyva-Perea, Jessica Jazmín; Miranda-Félix, Patricia Enedina; Gutiérrez-Valverde, Juana Mercedes; Ortiz-Félix, Rosario Edith; Mancillas-Berrelleza, Luis Antonio (Revista Cuidarte, 2025)
Highlights • It is essential to identify problems in the pharmacological treatment process so that healthcare professionals can provide appropriate care. • Satisfaction with pharmacological treatment among adults with type 2 diabetes may optimize disease control. • Given the high percentage of adults with uncontrolled blood glucose, further research and actions are needed in this population group. • Active listening can strengthen the healthcare professional-patient relationship. Introduction:The management of Type 2 Diabetes should be based on a person-centered approach to ensure the appropriate selection of pharmacological treatment. Satisfaction with pharmacological treatment is a patient-reported assessment measure that evaluates the treatment process and related factors, which may enhance adherence and glycemic control. Objective:To determine the strength of association between satisfaction with pharmacological treatment and adherence for glycemic control in adults with Type 2 Diabetes. Materials and Methods: A cross-sectional predictive study with model testing was conducted. A total of 146 participants with Type 2 Diabetes were enrolled using snowball sampling. The Diabetes Treatment Satisfaction Questionnaire (DTSQ), the Morisky Medication Adherence Scale (MMAS-4), and a sociodemographic and clinical data form were administered, and glycated hemoglobin level was measured. Associations were estimated using multiple linear regression.Results: Adherence to pharmacological treatment only predicted glucose control. The difference in glycated hemoglobin between adherent and non-adherent individuals was 0.22 lower in adherent individuals (β = -0.22, F = 2.95, p = 0.001).Discussion: The results differ from other studies that have reported subsequent changes in glycated hemoglobin associated with treatment satisfaction. Conclusions: The results differ from other studies that have reported subsequent changes in glycated hemoglobin associated with treatment satisfaction. How to cite this article: Leyva-Perea Jessica Jazmín, Miranda-Félix Patricia Enedina, Gutiérrez-Valverde Juana Mercedes, Ortiz-Félix Rosario Edith, Mancillas-Berrelleza Luis Antonio. Satisfaction and adherence to pharmacological treatment for glycemic control in adults. Revista Cuidarte. 2025;16(3):e4128. https://doi.org/10.15649/cuidarte.4128